ON TWO HII REGIONS NEAR THE NUCLEUS OF M82 - RECILLAS CRUZ, E; PEIMBERT, M (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1969)
Schmidt camera objective prism and direct photographic plates taken with different filters are used in this study of the nuclear regions of M82. In addition to the nuclear H II region, an extremely bright H II region 9.6" in diameter at 14" SW of the cent
BOL OBS TONAN TACUB
Keywords: REGIONS NEAR, NUCLEUS, M82; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS